2017
DOI: 10.1002/admi.201601035
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching Properties through Iodine Migrations of a Hybrid Perovskite Insulating Layer

Abstract: This study reports a low‐temperature processable, resistive switching (RS) device based on an inorganic–organic hybrid perovskite, i.e., methylammonium lead iodide (CH3NH3PbI3 or MAPbI3) via a fast deposition–crystallization method, as the multifunctional insulator layer to form metal/insulator/metal structure in which Al and p+‐Si wafer are used as the top and the bottom metal electrodes, respectively. The MAPbI3‐RS device shows acceptable RS characteristics with a switching window of 103 at a low voltage reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…All the materials were used as received without any purification. Recent research has shown that I − (0.1-0.6 eV) and MA + (0.5-0.8 eV) have low migration activation energies and several types of point defects in MAPbI3 have low formation energies, including vacancies (VPb, VMA, VI), interstitials (MAi, Ii), and antisubstitutions (PbI, MAPb) [13]. These point defects can cause shallow defect levels and then trap charges at these energy levels, revealing that in HOIPs, a strong potential application of photoresistors can be predicted.…”
Section: Preparation Of Microrodsmentioning
confidence: 99%
“…All the materials were used as received without any purification. Recent research has shown that I − (0.1-0.6 eV) and MA + (0.5-0.8 eV) have low migration activation energies and several types of point defects in MAPbI3 have low formation energies, including vacancies (VPb, VMA, VI), interstitials (MAi, Ii), and antisubstitutions (PbI, MAPb) [13]. These point defects can cause shallow defect levels and then trap charges at these energy levels, revealing that in HOIPs, a strong potential application of photoresistors can be predicted.…”
Section: Preparation Of Microrodsmentioning
confidence: 99%
“…As an intermediate active material for a new generation of resistive random-access memory, organic–inorganic halide perovskite materials show a more remarkable resistance switching effect than traditional active materials due to their simple preparation process and the unique current-voltage hysteresis property caused by rapid ion migration and defects [ 11 , 12 , 13 , 14 , 15 , 16 ]. However, the application of the organic–inorganic halide perovskite materials in the resistance switching memory devices is limited due to the hygroscopicity and relatively poor thermal stability of organic cations [ 17 , 18 , 19 , 20 ]. According to the reported literature, the organic cations in the organic–inorganic halide perovskite materials can be replaced by inorganic cations such as Cs to improve the stability of the material, which shows that the all-inorganic halide perovskite material (CsPbX 3 , X = Cl, Br, and I) as an intermediate active material of resistance random-access memory devices has potential advantages [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in addition to its photovoltaic applications, organic–inorganic metal halide perovskite has been demonstrated as an active layer in ReRAM cells, showing tunable and remarkable memory properties and flexibility [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Based on the various material systems of perovskite, the constituent tuning provides an influential factor in controlling the memory property; [ 34 ] but most of the research about the memory application of the three-dimensional (3D) perovskites is still focused on MAPbI 3 [ 22 , 23 , 25 , 27 , 28 , 29 , 30 ]. Besides MAPbI 3 , some researchers have reported on the MAPbX 3 based ReRAM where X = Br or Cl or a mixture of I, Br, or Cl [ 21 , 26 , 33 ].…”
Section: Introductionmentioning
confidence: 99%